Design and Kinetic Analysis of the Parallel Mechanism for Sorting and Transmitting of Automobile Parts - Ju Tao; Shen Huiping; Li Tao (Jixie chuandong)
In order to realize the intelligent sorting and transmitting of automobile parts, a new full-hinge translation-rotation (1T1R) parallel mechanism is proposed, which is simple in structure and partially decoupled in motion. Firstly, based on the topological design theory and method of azimuth characteristic equation, a two-degree-of-freedom 1T1R parallel mechanism is designed and analyzed. Secondly, based on the topological characteristic kinematics method, the positive symbolic position solution of the mechanism is solved. The workspace and singularity of the mechanism are calculated. Finally, the driving torque and the supporting reaction at the joint of the sub kinematic chain (SKC) are obtained by using the sequential simple open chain method based on the virtual work principle. The research lays a foundation for the design and research of the parallel mechanism of automobile parts.